SISTEM PEMESANAN BERBASIS WEB PADA USAHA SEFIE’S KICHEN BENGKULU - Atang Khotami (UNIVED Press, 2023)
Abstract: Web technology on the internet plays a very important role, which allows organizations or companies to enter the market in an easy, inexpensive way, and without geographical restrictions, all of which will be in what is called cyberspace, ordering products has a smooth work process. without being separated in the computerization process, of course it will simplify the product ordering process. Therefore the author makes use of a web-based ordering system in the Bengkulu sefie's kitchen business which can provide active support for the smooth running of product sales efforts in the snack food business. By creating a web-based ordering system, it will help providing data processing related to ordering products, increasing the effectiveness of selling Saefie's Kichen Bengkulu products.